Developing Religious Moderation-Based Reading Materials for English Instruction at MA Awaluddin Kubu Raya - Kholifuddin Roma; Segu, Segu (Program Studi Tadris Bahasa Inggris Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2025)
This study focuses on developing English instructional materials based on religious moderation for students at MA Awaluddin Kubu Raya. Itused a design and development approach, guided by the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The work was limited to the first three stages, which are Analysis, Design, and Development, to create and validate the new learning materials through expert evaluation. While the ADDIE framework provided a clear and thorough process for development, the later stages of implementation and classroom assessment were not conducted. These remaining phases are noted as important next steps and a key limitation of this study. The materials were designed by integrating linguistic elements with the four pillars of religious moderation, namely national commitment, tolerance, non-violence, and appreciation of local culture. The product was validated by three experts: an English language content expert, an education specialist, and a religious moderation expert from the Forum for Religious Harmony (FKUB). The results indicate a feasibility level of 95.00%, categorized as highly appropriate, with scores of 96.75% for content, 93.25% for linguistic aspects, and 95.00% for design and media. The final product, Reading Comprehension Lessons Based on Religious Moderation, comprises ten thematic reading units designed to foster tolerance, national values, peaceful interaction, and cultural respect. The findings confirm that the developed materials are strong in both theory and content, according to expert evaluation. They are therefore deemed suitable and ready for initial implementation and pilot testing with students. The product offers a validated model as an alternative resource for English language teaching in madrasah settings.